Planning Development of Creative Park in JungleFest Bogor - Sari, Dhanik Puspita; Rizki, Antonius; Pambudi, Bondan; Djati, Sundring Pantja (Technium Social Sciences Journal, 2022)
A lot of people who need a short escape with full experience make a theme park always wanted to visit. Located in Bogor city, nearby the capital city of Indonesia makes Junglefest is one of the urban destinations to be visited. In order to increase the number of visitors, they planned to add more attractions inside their territory, and will be called “Creative Park”. This paper is giving a short review regarding the planning development of this Creative Park in a form of a theme park. Starting with mapping the potential analysis, planning steps, development steps, and evaluating steps by looking into the impact arising from the activities done in the park